2018
DOI: 10.3390/ijms19071959
|View full text |Cite
|
Sign up to set email alerts
|

Transmembrane TNF and Partially TNFR1 Regulate TNFR2 Expression and Control Inflammation in Mycobacterial-Induced Pleurisy

Abstract: Pleural tuberculosis is one of the most frequent forms of extra-pulmonary tuberculosis observed in patients infected with Mycobacterium tuberculosis. Tumor Necrosis Factor (TNF) is a crucial cytokine needed to control tuberculosis infection that remains a leading cause of morbidity and mortality worldwide. TNF blockade compromises host immunity and may increase the risk of reactivation of latent infection resulting in overt pulmonary, pleural and extra-pulmonary tuberculosis. While TNF signaling is mainly cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…In contrast, TNF-α -238 A allele was less detected in the GC group and was associated with low TNF-α levels, we can suggest that the elevation of circulating TNF-α is implicated in the promotion of GC and not in its regression as a double act of this cytokine vis-a-vis malignant and precancerous cell. It seems that tmTNF-α reduces the severity of inflammatory reactions and tumor growth, while sTNF-α stimulates those processes (Ardestani et al, 2013;Horiuchi et al, 2010;Uysal et al, 2018;Yamamoto et al, 2004;Yu et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, TNF-α -238 A allele was less detected in the GC group and was associated with low TNF-α levels, we can suggest that the elevation of circulating TNF-α is implicated in the promotion of GC and not in its regression as a double act of this cytokine vis-a-vis malignant and precancerous cell. It seems that tmTNF-α reduces the severity of inflammatory reactions and tumor growth, while sTNF-α stimulates those processes (Ardestani et al, 2013;Horiuchi et al, 2010;Uysal et al, 2018;Yamamoto et al, 2004;Yu et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The different TNF-α isoforms can have different effects on inflammatory responses and tumor development. Based on several studies, it seems that tmTNF-α reduces the severity of inflammatory reactions and tumor growth, while sTNF-α stimulates those processes (Ardestani et al, 2013;Horiuchi et al, 2010;Uysal et al, 2018;Yamamoto et al, 2004;Yu et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…At present, it is not clear whether the migration or function of CD3 + TCRαβ + and CD3 + TCRαβ − MDM is mediated only by TNFR1, TNFR2 or both together. We have reported that the axis tmTNF/TNFRs can be self-regulated during BCG-induced pleurisy, tmTNF restores the normal expression of TNFR2 on myeloid cells, and in turn, the absence of TNFR1 affects the expression of TNFR2, leading to exacerbated inflammation and bad control of the infection (32). We have also shown that in the context of BCG pleural infection, the interaction of tmTNF-expressing MDSC with CD4 + T cells expressing TNFR2 (expression of TNFR1 was dispensable) leads to attenuating the excessive inflammatory response (10).…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence indicates that tmTNF-α exerts protective effect against bacterial infections, chronic inflammation, and autoimmunity diseases 24 . As a ligand, tmTNF-α attenuates the inflammatory processes caused by mycobacterial pleurisy in association with TNFR2 expression on myeloid cells 25 . Interactions between tmTNF-α and TNFR2 are important for the expansion and function of Treg cells 26 and for activation of myeloid-derived suppressive cells to exert immune suppressive activities 27 .…”
Section: Discussionmentioning
confidence: 99%